Threshold theory: Modelling risk attitude - Tomasz Kasprowicz; Andrzej Bednorz (e-Finanse: Financial Internet Quarterly, 2017)
In this paper we offer an alternative framework for examining why risk matters in the decisions of economic agents, and how the agent's risk attitude affects his decisions. This 'Threshold Theory' framework is based on a real options approach and the observation that in many situations an agent faces one or more thresholds in the payoff function. These thresholds influence the agent's risk attitude. The theory's predictions help to explain many anomalies that the standard expected utility model cannot. Threshold Theory can also model behavior in contexts such as individual investor decisions, corporate governance and other agency problems. Further, we examine CEO decisions as a function of time to the CEO's retirement to test predictions of the Theory.
Keywords: G31; M15; D01; 330; Decision-making under uncertainty; real options; agency theory; CEO behavior